DIVERSITAS JENIS GASTROPODA DI PANTAI KALALA KECAMATAN WULLA WAIJELU SEBAGAI SUMBER BELAJAR DALAM BENTUK ENSIKLOPEDIA - Jati Atahau, Septiani; Tamu Ina, Anita; Ndjoeroemana, Yohana (Jurnal Biogenerasi, 2024)
This study aims to describe the Gastropod Diversity at Kalala Beach, East Sumba Regency as a Learning Resource in the form of an Encyclopedia. The type of research used in this study is a type of ecological research with a quantitative descriptive approach. The sampling technique in the study used purposive sampling technique and sampling using the quadrant method (m2). The results showed that there were 300 individuals from 12 species, namely, Ergalatax contracta, Tectus pyramis, Nassarius coronatus, Pisania striata, Canarium labiatum, Canarium olydium, Terebra subulata, Clanculus corallinus, Neverita josephinia, Ranella olearia, Atys naucum and Monetaria annulus. The highest density value is in the Canarium labiatum species, which is 0.333, the highest frequency in the Canarium labiatum species is 0.66, while the lowest density is Ranella olearia at 0.066 with the lowest frequency of Tectus pyramis, Clanculus corallinus and Neverita josephinia at 0.4. The gastropod diversity found at Kalala Beach, with a Diversity Index (H') value of 2.019, is classified as moderate. The research results can be utilized as a Biology learning resource in the form of an Encyclopedia. The results of the Encyclopedia validation test by validators first and second gave the same value of 88.3%. This value indicates that the Encyclopedia is suitable for use